Peculiarities of spectral reflectance of fractions with sizes from 20 to 5,000 microns in soil samples - I. Yu. Savin; M. A. Shishkin; D. V. Sharychev (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
By the example of arable horizon samples taken from three soil types (sod-podzolic, gray forest, and leached chernozem) the peculiarities of electromagnetic waves reflection from their different particle size fractions were studied. The extraction of fractions by dry sieving was carried out using Retsch AS 200 BASIC equipment. As a result, 14 fractions ranging in size from less than 20 microns to more than 5,000 microns were isolated. Spectral reflectance was determined for each fraction and for the soil sample before sieving in the electromagnetic wave range from 350 to 2,500 nm using a SR-6500 field spectroradiometer (Spectral Evolution, USA). Analysis of similarities and differences in the obtained spectral reflectance curves of individual fractions was carried out using their visual analysis, the method of similarity dendrogram construction, as well as regression analysis between light reflectance and fraction particle size. It was confirmed that at a more detailed level of analysis compared to the one carried out by other researchers earlier, the general patterns of light reflectance of the samples do not change. A higher reflection of waves by thinner fractions and a lower reflection by more coarse fractions are observed. At the same time, spectral reflection curves for individual fractions are out of the general pattern, the level of intensity of local extremes of the curves’ changes. This confirms the difference of the material composition, which forms the color of soils, of these fractions from others. The color of the mixed sample is a spectral mixture of colors of its separate fractions. Presumably, this is the main reason for such a phenomenon as change of spectral reflectivity of open surface of soils under the influence of atmospheric precipitation.